38 Using Canine Olfaction to Detect Bovine Respiratory Disease: A Pilot Study. (8th March 2022) - Juge, Aiden E; Hall, Nathan; Richeson, John; Daigle, Courtney L
Abstract: Bovine respiratory disease (BRD) is the leading cause of morbidity and mortality in feedlot cattle and is therefore a major welfare and economic concern. Identification of BRD-affected cattle using clinical illness score is problematic, and speed and cost constraints limit the feasibility of many diagnostic approaches. Dogs can rapidly identify humans and animals affected by a variety of diseases based on scent. Canines' olfactory systems can distinguish between patterns of volatile organic compounds produced by diseased and healthy tissue. In this pilot study, two dogs were trained for seven months to discriminate between nasal swabs from cattle that developed signs of BRD within twenty days of feedlot arrival and swabs from cattle that did not develop BRD signs within three months at the feedlot. Nasal swabs were collected during cattle processing upon arrival to the feedlot and were stored at -80°C. Dogs were presented with sets of one positive and two negative samples and were trained using positive reinforcement to hold their noses on the positive sample. The dogs performed moderately well in the final stage of training, with accuracy for Dog A of 0.817 and Dog B of 0.647. During a double-blind detection test, dogs evaluated 123 unique and unfamiliar samples that were presented as 41 sets (3 samples per set), with both the dog handler and data recorder blinded to the positive sample location. Each dog was tested twice on each set of samples. Detection test accuracy was slightly better than the 0.333 expected by chance for Dog B at 0.451 (95% CI: 0.341-0.565) and was no better than chance for Dog A at 0.390 (95% CI: 0.284-0.504. Overall accuracy was 0.421 (95% CI: 0.344-0.500). While dogs showed some ability to discriminate between BRD-affected and healthy cattle using nasal swabs, the complexity of this task suggests that more testing is needed before identifying whether dogs could be effective as a screening method for BRD.